Baseball Blowup - Jake Maddox (Stone Arch Books, 2023)
Malcolm loves two things--baseball and science. He's always studying the stats and coming up with ideas to help his team gain an advantage over the competition. But when Malcolm's homemade glove oil causes a major blowup with his teammates, he must find a way to win back their trust. Leaning into science and statistics, he decides to try a new type of pitch to keep batters off balance during his next start. Will Malcolm's secret pitch prove to be a game winner or just another failed experiment? Find out in this exciting, easy-to-read chapter book by Jake Maddox!
Keywords: Sport Stories -- Sport Stories